2019
DOI: 10.1101/698209
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

PDAC-ANN: an artificial neural network to predict Pancreatic Ductal Adenocarcinoma based on gene expression

Abstract: Background: Although the pancreatic ductal adenocarcinoma (PDAC) presents high mortality and metastatic potential, there is a lack of effective therapies and a low survival rate for this disease. This PDAC scenario urges new strategies for diagnosis, drug targets, and treatment. Methods:We performed a gene expression microarray meta-analysis of the tumor against healthy tissues in order to identify differentially expressed genes shared among all datasets, named core-genes (CG). We confirmed the pancreatic expr… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 65 publications
0
13
0
Order By: Relevance
“…Only AHNAK2 involved in this signature have been previously investigated in PDAC. Several studies in PDAC have con rmed AHNAK2 as an oncogene [23,24]. Lu et al [24] indicated that AHNAK2 is upregulated in 79 PDAC tissues compared with adjacent normal tissue, and patients with high AHNAK2 expression had worse OS.…”
Section: Discussionmentioning
confidence: 99%
“…Only AHNAK2 involved in this signature have been previously investigated in PDAC. Several studies in PDAC have con rmed AHNAK2 as an oncogene [23,24]. Lu et al [24] indicated that AHNAK2 is upregulated in 79 PDAC tissues compared with adjacent normal tissue, and patients with high AHNAK2 expression had worse OS.…”
Section: Discussionmentioning
confidence: 99%
“…Data collection and DEGs/DEMs/tDEGs/tDEMs analysis Gene expression pro les were downloaded from the GEO public database (http://www.ncbi.nlm.nih.gov/geo/) and the inclusion criteria were as follows: (1) pancreatic cancer, (2) January 1, 2009 to December 31, 2019, (3) homo sapiens, (4) tissue, (5) sample count exceeds 30, (6) mRNA or miRNA expression data available. As a result, a total of 5 datasets were selected, which included GSE62165, GSE15471, GSE24279, GSE32676 and GSE32678.…”
Section: Methodsmentioning
confidence: 99%
“…It has revolutionized RNA and DNA studies and also been extensively conducted as an e cient tool for exploration of genes and biological processes of human diseases, which contribute to uncover the underlying biological mechanisms. Several studies reported the differentially expressed genes (DEGs) and differentially expressed microRNA (DEMs) of PC separately during the past years [2][3][4] . However, there remain questions about the interaction between DEGs and DEMs during the progression of the PC.…”
Section: Introductionmentioning
confidence: 99%
“…Down syndrome is a chromosomal disorder caused due to the presence of all or some part of an extra 21st chromosome. Pancreatic ductal adenocarcinoma (PDAC) has a low survival rate mainly due to inefficient therapies 87 . For the identification of Core Genes (CG), a meta‐analysis tumor against normal tissue has been carried out and as result, 05 genes (KRT 19 , LAMC 2 , S 100 P, AHNAK 2, and LAMB 3 ) are identified.…”
Section: Applications Of Anns In the Field Of Medicinementioning
confidence: 99%